Oxytocin increases liking for a country's people and national flag but not for other cultural symbols or consumer products - Ma, Xiaole; Luo, Lizhu; Geng, Yayuan; Zhao, Weihua; Zhang, Qiong; Kendrick, Keith M. (Frontiers in Behavioral Neuroscience, 2014)
The neuropeptide oxytocin enhances in-group favoritism and ethnocentrism in males. However, whether such effects also occur in women and extend to national symbols and companies/consumer products is unclear. In a between-subject, double-blind placebo controlled experiment we have investigated the effect of intranasal oxytocin on likeability and arousal ratings given by 51 adult Chinese males and females for pictures depicting people or national symbols/consumer products from both strong and weak in-groups (China and Taiwan) and corresponding out-groups (Japan and South Korea). To assess duration of treatment effects subjects were also re-tested after one week. Results showed that although oxytocin selectively increased the bias for overall liking for Chinese social stimuli and the national flag, it had no effect on the similar bias towards other Chinese cultural symbols, companies and consumer products. This enhanced bias was maintained one week after treatment. No overall oxytocin effects were found for Taiwanese, Japanese or South Korean pictures. Our findings show for the first time that oxytocin increases liking for a nation’s society and flag in both men and women, but not that for other cultural symbols or companies/consumer products.